CHILDFREE DAN RUANG PUBLIK: RESEPSI WARGANET TERHADAP PEREMPUAN CHILDFREE DALAM KOLOM KOMENTAR PADA KANAL YOUTUBE METRO TV NEWS - Nurul Ilmi Sudirman (Universitas Katolik Soegijapranata, 2024)
This study is motivated by the childfree choice for women which is now starting to become a new lifestyle among young Indonesian couples. This phenomenon is of course inversely proportional to the normative culture of Indonesian society, which expects married adults to have children. The childfree phenomenon then became a topic of conversation among netizens, especially in the YouTube comments space. This research aims to analyze and understand netizens' reception of childfree women in the video comment space entitled